Study on Surrounding Rock Stability Mechanism of Gob-Side Entry Retaining with Prefabricated Fracture - Hao Wu; Chuanqu Zhu; Qingfeng Li (Advances in Civil Engineering)
To study the optimal layout of prefabricated roof cutting line in gob-side entry retaining with roof cutting and pressure relief, based on the engineering geological conditions of 5249 working face in Beipingdong Coal Mine of Baoyuan Mining Company, the FLAC3D numerical simulation method was used to study the surrounding rock characteristics of gob-side entry retaining under different layout conditions of prefabricated roof cutting line, and the optimal layout of prefabricated roof cutting line in gob-side entry retaining with roof cutting and pressure relief was proposed. The results show that the roadway floor has a certain degree of floor heave with the mining process under different angles. The angle between the prefabricated roof cutting line and the vertical line of the roadway has little effect on the lateral displacement of the coal body in the mining process of gob-side entry retaining. When the cutting angle is 10°, the stability of the surrounding rock of gob-side entry retaining is more stable than that of other angles, and the plastic range is small. The stability of the surrounding rock of the roadway is more stable than that of other angles, which is conducive to the safe mining of 5249 working faces in Beipingdong Coal Mine.